THE RELATIONSHIP BETWEEN IEC FAMILY SERVICES AND IMPROVING ABILITY AND INTEREST IN BECOME A FAMILY ACCEPTOR IN THE WORKING AREA OF LAMPAHAN PUBLIC HEALTH CENTER, TIMANG GAJAH DISTRICT, BENER MERIAH REGENCY, ACEH PROVINCE IN 2023 - Nurmala Sari; Surbakti, Imran Saputra; Surbakti, Riski Tiara; Munthe, Juliana; Bate’e, Cantik Marlin; Hasibuan, Nur Adillah; Saibatul Aslamia (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Background: Based on a preliminary survey conducted in the Working Area of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency in 2023, it was found that the number of women of childbearing age was 3161 people and 2,495 KB acceptors (79%), a survey of 10 KB acceptors. using KB Injections as many as 3 people (30%), Pills 3 people (30%), IUD 2 people (20%), Implants 2 people (20%). Contap 1 person (10%) and Condoms 2 people (20%), with the number of children 2-3 people. with an average job of housewives, stated that the desire to use contraceptives was due to their own will and according to the midwife the type of contraception that can be used, from the preliminary survey it was found that there were still few who used long-term contraception, because acceptors felt they were not ready and were afraid to use long-term contraception. Method: This study is an observational/survey study, where data is collected from respondents using questionnaires without any intervention on the research subjects. The population of this study is 165 family planning acceptors in the working area of the Lampahan Community Health Center, Timang Bajah District, Bener Meriah Regency, Aceh Province in 2023. The sampling method was determined by purposive sampling and the Slovin formula with a margin of error of 5% or 0.05. The data analysis method used is Chi-square. Result : There is a relationship between educational information communication and the ability and interest of KB acceptors seen from the age of the Lampahan Health Center Working Area, Timang Gajah District, Bener Meriah Regency, Aceh Province in 2023 where the p-value is 0.036 for communication, 0.033 for information and 0.036 for education (p <0.05). There is a Relationship between Communication and Education Information and the Ability and Interest of KB Acceptors as seen from the number of children in the Working Area of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency, Aceh Province in 2023 where the p-value is 0.012 for communication and education and 0.011 for information (p <0.05). There is a Relationship between Communication of Educational Information and the Ability and Interest of KB Acceptors as Seen from the History of Diseases in the Working Area of the Lampahan Health Center, Timang Gajah District, Bener Meriah Regency, Aceh Province in 2023 where the p-value is 0.001 for communication and education and 0.021 for information (p<0.05).